When is a debt bad or doubtful in terms of the Income Tax Act? - Hartley, Ryan (Department of Finance and Tax, 2019)
Bad debt deductions and doubtful debt allowances provide relief to taxpayers who would be subject to income tax on amounts accrued to them which may never be received. No definition of a bad or doubtful debt is provided in the Income Tax Act. This dissertation considered current legislation, historical court cases, academic writing and the views expressed by SARS through explanatory memoranda and directives in order to establish when a debt becomes bad or doubtful and the extent of the relief granted. This dissertation also considered the future of the doubtful debt allowance in light of the change of accounting standards from IAS 39 to IFRS 9. There are no specific requirements for a debt to become bad or doubtful. Whether a debt is bad is a factual question taking into account all relevant facts. Whether a debt is doubtful and the extent of the allowance granted is determined by the Commissioner, but that determination must be reasonable. The Commissioner relies on IAS 39 rules of impairment as the starting point for determination of a doubtful debt allowance. IFRS 9 determines impairment in a significantly different manner to IAS 39, abandoning the requirement that a “loss event” must have occurred. Adoption of IFRS 9 will result in a change to the determination of doubtful debt allowances, for example, by reducing the generally accepted rate of 25% of identified doubtful debts or by requiring the taxpayer to compile a list of debts which would have qualified as doubtful under IAS 39.